Understanding and Factors of Safety Riding Behavior Among Students - Prihastini, Komang Angga; Haryawan, I Gusti Agung (Indonesian Journal of Global Health Research, 2024)
Safety ridingis one method to provide knowledge and broaden horizons for teenagers who often ignore good driving behavior.Bali International University is one of the private campuses in Baliwhich has students passing by on motorbikes every day. The initial survey found that students who came to campus behaved unsafely when driving and it was found that students did not understand safety riding and there were students who did not have a driving license (SIM). The aim of this research was to carry out this research. Efforts can be made to prevent accidents while driving. The method used is quantitative research with a cross-sectional observational analytical method. The sample is students at UNBI who can drive two-wheeled vehicles and a total of 165 respondents were obtained. The results of this research are between knowledge and safe riding. isthat there is no relationship pvalue 0.455, namely > 0.05, behavior and safety riding have a significant relationship pvalue 0.03, namely <0.05, ownership of a SIM C and safety riding have a significant relationship pvalue 0.003, namely <0.05. Safety Riding It can be an understanding for students to continue driving safely by having a SIM C, knowing the applicable regulations to minimize the risk of accidents and the campus can provide